The LC-MS/MS Profile and Total Phenolic Content of Telang Flower Extract and Roselle as NPC1L1 Inhibitor Candidate - Erna Susanti; Meiria Istiana Sari (Faculty of Medicine, University of Jember, 2022)
Inhibition of atherogenesis can be done through several mechanisms, one of which is inhibiting intestinal cholesterol absorption through inhibition of NPC1L1. The activity of Telang flower extract in overcoming various problems of degenerative diseases, especially cardiovascular disease, has been proven by many scientific studies. Likewise, related to the activity of Rosella flowers. Previous research conducted by researchers showed the potential of Rosella flower extract as an LXR agonist, one of the pathways that play a role in NPC1L1 inhibition. The combination of the two extracts is expected to increase its activity as a candidate for NPC1L1 inhibitor. The purpose of this study was based on the results of the determination of total phenolic levels and the characterization of the active compounds with LC MS/MS extracts of telang flower and rosella, which are expected to be developed into further research in vivo to strengthen scientific evidence so that they can be developed into phytopharmaca preparations. Instrumentation analysis method with LC-MS/MS to identify the content of active compounds and determination of total phenolic content with Folin ciocalteu in order to obtain standardized extracts of telang flower and roselle. The results of this study showed that the total phenolic content based on the largest order was purple rosella flower extract (114.129.35 ± 266.20 g GAE), a combination of purple rosella and telang flower extract (101.760.58 ± 116.09 g GAE), telang flower extract (90.477.41 ± 107.38 g GAE) and extract red rosella flowers (84,601.00 ± 266.91 g GAE). The combination of extracts showed reduced total phenolic content compared to the single extract. The phenolic content in each extract affected the total phenolic in the combination of extracts. 8 anthocinin compounds were identified in both the telang flower extract and the rosella flower extract. Keywords: NPC1L1 inhibitor, telang, extract, Roselle, total phenolics, LC-MS/MS, atherogenesis